2013
DOI: 10.1016/j.biomaterials.2013.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Differential and synergistic effects of mechanical stimulation and growth factor presentation on vascular wall function

Abstract: We investigated the hypothesis that immobilizing TGF-β1 within fibrin hydrogels may act in synergy with cyclic mechanical stimulation to enhance the properties of vascular grafts. To this end, we engineered a fusion TGF-β1 protein that can covalently anchor to fibrin during polymerization upon the action of factor XIII. We also developed a 24-well based bioreactor in which vascular constructs can be mechanically stimulated by distending the silastic mandrel in the middle of each well. TGF-β1 was either conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Previous work in our laboratory has shown that fibrin immobilized TGF-b1-promoted MSC differentiation to SMCs uniformly throughout fibrin rings, eliminating growth factor diffusion limitations. 33,42 VEGF has been used to promote angiogenesis in many previous studies, however, neovessels formed only in the presence of VEGF have been shown to be unstable and degrade rapidly in vitro, and at a slower extent in vivo. This is likely due to the lack of pericytes and SMCs, which typically enwrap neovessels within the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in our laboratory has shown that fibrin immobilized TGF-b1-promoted MSC differentiation to SMCs uniformly throughout fibrin rings, eliminating growth factor diffusion limitations. 33,42 VEGF has been used to promote angiogenesis in many previous studies, however, neovessels formed only in the presence of VEGF have been shown to be unstable and degrade rapidly in vitro, and at a slower extent in vivo. This is likely due to the lack of pericytes and SMCs, which typically enwrap neovessels within the body.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin has been extensively studied as a scaffold and a number of studies have shown that fibrin is a growth factor carrier for tissue regeneration. 33,42 In addition, fibrin has also been used to deliver stem cells for bone tissue engineering. 43,44 Ideally, incorporation of a vascularized network into engineered bone substitutes to mimic the structure of natural bone tissue is necessary to promote rapid bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the initial rate of compaction was ∼2.38% per hour for WT cells but less than half of that at ∼1.01% per hour for Cdh11 −/− cells. We also measured the mechanical properties and collagen content of tissue constructs prepared from Cdh11 −/− or WT mouse dermal fibroblasts, as we described in previous publications (DiazChavez et al, 2008;Liang et al, 2013;Koobatian et al, 2016). To this end, we prepared cylindrical tissue equivalents by embedding cells in fibrin hydrogels that were polymerized around cylindrical mandrels and cultured in the presence of TGF-β1 for 2 weeks.…”
Section: Cdh11mentioning
confidence: 99%
“…Experimental triplicates or quadruplicates with each group were used to measure area of fibrin gel as a fraction of total area (A/A 0 ) of a standard 24-well plate (A 0 =2 cm 2 ). These gels were further cultured in vessel medium (Liang et al, 2013) in the same plates for 14 days, to allow for collagen deposition and remodeling.…”
Section: Fibrin Gel Compactionmentioning
confidence: 99%
“…The medium was changed the following day after gel polymerization, and every other day thereafter. TEV constructs on the 24-PP were kept under static conditions for 1 week, and then pulsed for 1 week periodically (0.3 s/1.7 s distended/rested as reported previously 21,30,31 ).…”
Section: Preparation Of Tissue-engineered Vessels On the 24-ppmentioning
confidence: 99%